Rigor or Restriction: Examining Close Reading With High School English Language Learners. Issue 4 (30th November 2016) - Thomason, Betty; Brown, Clara Lee; Ward, Natalia
Abstract : English language learners (ELLs) are the fastest growing student subgroup in the United States, and public schools have the challenging task of teaching ELLs both English language and academic content. In spite of the attention given to improving outcomes for ELLs, the achievement gap between ELLs and native English speakers persists, especially in reading. Currently, 43 states have adopted the Common Core State Standards (CCSS; National Governors Association Center for Best Practices & Council of Chief State School Officers, 2010 ) for language arts and English curriculum (Achieve, 2013). To address achievement gaps in reading, CCSS recommend a close reading procedure that involves repeated readings of a single complex text to increase student reading comprehension of expository texts. In this pilot study, the researchers examined the appropriateness of close reading procedures prescribed by CCSS for ELLs. Six high school ELLs participated in two units of study in an English as a second language U.S. history class that implemented close reading procedures. The researchers found no evidence of either improved reading comprehension or U.S. history content knowledge. The participants also reported a loss of motivation to read after participating in close reading.